2012
DOI: 10.1002/micr.21951
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar nerve injuries in guyon canal: A report of 32 cases

Abstract: Early diagnosis and surgical treatment with careful dissection of the ulnar nerve branches within the canal is very important. Adequate exposure is usually required to repair the nerve in the Guyon canal. Nerve grafting in this level could give analogous results as the end-to-end repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…43 In general, more proximal injuries do worse, as do repairs requiring nerve grafts and those done in a delayed fashion. 44,45 Kim and colleagues, 25 in a study of 654 ulnar nerve lesions, have shown that functional recovery of grade M3 or better motor recovery is greatest when the injury requires only neurolysis (92% of patients), followed by primary repair (72% of patients), and then those injuries requiring nerve grafting (67% of patients). Ruijs and colleagues, 44 in their meta-analysis of 23 publications, found that ulnar nerve injuries gave a 71% lower chance of motor recovery than median nerve injuries.…”
Section: Diagnosismentioning
confidence: 96%
“…43 In general, more proximal injuries do worse, as do repairs requiring nerve grafts and those done in a delayed fashion. 44,45 Kim and colleagues, 25 in a study of 654 ulnar nerve lesions, have shown that functional recovery of grade M3 or better motor recovery is greatest when the injury requires only neurolysis (92% of patients), followed by primary repair (72% of patients), and then those injuries requiring nerve grafting (67% of patients). Ruijs and colleagues, 44 in their meta-analysis of 23 publications, found that ulnar nerve injuries gave a 71% lower chance of motor recovery than median nerve injuries.…”
Section: Diagnosismentioning
confidence: 96%
“…Electrodiagnostic changes of the ulnar nerve have been reported in numerous case reports throughout the literature. 2,4,6,27 However, these studies are retrospective, and some have incompletely evaluated the ulnar nerve. Although many studies evaluated motor function to ADM, fewer studies report analyzing the deeper motor branch of the ulnar nerve to FDI.…”
Section: Electrodiagnostic Studiesmentioning
confidence: 99%
“…1 Since then, there have been numerous case reports describing this phenomenon, some of which refer to this condition as "handlebar palsy." [2][3][4][5] For the purposes of this article, we consider these terms interchangeable.…”
mentioning
confidence: 99%
“…A positive Froment sign, characterized by interphalangeal flexion when a patient attempts to pinch a thin object, also demonstrates weakness in these muscles, and the flexor pollicis longus compensates for the weakened muscles. 35 Inability to cross the index and middle fingers may indicate deficient deep ulnar motor innervation of the first palmar and second dorsal interossei. Because the hypothenar muscles receive motor innervation at the origin of the deep motor branch of the ulnar nerve, 3 intact function in these muscles combined with weakness of the interosseous and adductor pollicis muscles indicates a lesion distal to the deep motor branch.…”
Section: Motor Examinationmentioning
confidence: 99%
“…Therefore, surgeons must be aware of the arborization patterns of the ulnar nerve to be prepared when anomalous anatomic structures and varied vascular courses are encountered during dissection. 35 Surgeons should carefully preserve the vascular supply to the ulnar nerve 14 and avoid injury to nerve branches in the wrist. 2…”
Section: Complicationsmentioning
confidence: 99%